Modeling and optimization of multi-component materials selection and sizing problem. (February 2020) - Giudice, Fabio; Fargione, Giovanna; Caponetto, Riccardo; La Rosa, Guido
Most of the research on materials selection has been characterized by a basic approach to the problem, isolating material choice from the other design variables, and focusing on single components. Instead, a complete approach aimed at optimizing material selection cannot be set aside from component sizing, and the analysis of constraints between components, that characterize the sub-assemblies or the whole system, and can influence the material choice itself. In this paper, a structured method to approach the simultaneous materials selection and sizing optimization of multi-component assemblies is proposed. It is based on a modeling of the problem, fully generalized in its formalization, so as to be applicable to the various cases, and formulated in order to take into account the systemic vision that must have the optimal choice in a multi-component perspective, and its close connection with the sizing of geometric variables, to effectively meet the required performances. In this regard, an efficiency criterion, which provides for the choice of material and variables sizing gauged on real needs, is also introduced. After presenting the framework and formalization of the method, the problem of searching for the best solution has been discussed. With regard to this, a genetic algorithm has been specifically developed according to the peculiarities of the generalized formulation, with the aim of enhancing the heuristic potential of the concurrent material choice and sizing approach in multi-component environment, in the search for the optimal solution. The application to a sub-system of a widely used plant device is reported in detail, so that use and capacity of the structured method are detailed and discussed.